2020
DOI: 10.3390/nu13010106
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Sociodemographic, Lifestyle, and Health-Related Determinants among People with Depression in Spain: New Evidence from a Cross-Sectional Population-Based Study (2011–2017)

Abstract: The role of diet quality in depression is an emerging research area and it appears that diet quality could be an important modifying factor. The aims of this study were to report the prevalence of diet quality among individuals with and without a self-reported diagnosis of depression aged from 16 to 64 years old in Spain, to analyze the time trends of the frequency of food consumption and diet quality from 2011 to 2017 in individuals with a self-reported diagnosis of depression, and to explore the associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 105 publications
(115 reference statements)
0
4
0
1
Order By: Relevance
“…Concerning sleep quality, two studies have shown an association of higher adherence to the Mediterranean diet during pregnancy [26] and food security with sleep quality [27], respectively; a third study from our group provided the first evidence of a potential role played by dietary polyphenol content in sleep quality [28]. Diet quality has also been related to depression in two studies: Cebrino et al [29] reported that non-depressive individuals had a higher diet quality than depressive ones in a nationwide cross-sectional study conducted in Spain; in the study of Marozoff et al [30], the authors showed that increasing Healthy Eating Index-Canada scores were associated with fewer physician visits for depression in a prospective investigation of adults living in Alberta (Canada).…”
mentioning
confidence: 74%
“…Concerning sleep quality, two studies have shown an association of higher adherence to the Mediterranean diet during pregnancy [26] and food security with sleep quality [27], respectively; a third study from our group provided the first evidence of a potential role played by dietary polyphenol content in sleep quality [28]. Diet quality has also been related to depression in two studies: Cebrino et al [29] reported that non-depressive individuals had a higher diet quality than depressive ones in a nationwide cross-sectional study conducted in Spain; in the study of Marozoff et al [30], the authors showed that increasing Healthy Eating Index-Canada scores were associated with fewer physician visits for depression in a prospective investigation of adults living in Alberta (Canada).…”
mentioning
confidence: 74%
“…Entre idosos de Santa Catarina no ano de 2016, fatores como não ter uma alimentação saudável, apresentar padrão de sono comprometido e volumes menores de prática de atividade física impactaram na ocorrência de SD 52 . O exercício físico, especificamente, tem sido fortemente apontado como fator de proteção à ocorrência de SD 53,54 , e entre professores de Barretos foi observada alta prevalência de inatividade física, estando o sedentarismo associado a pior qualidade de vida 55 .…”
Section: Resultsunclassified
“…Among the elderly in Santa Catarina in 2016, factors such as not having a healthy diet, a compromised sleep pattern and lower volumes of physical activity had impacts on the occurrence of DSs 52 . Physical exercise, specifically, has been strongly indicated as a protective factor against the occurrence of DSs 53,54 , and among teachers from Barretos, a high prevalence of physical inactivity was observed, with a sedentary lifestyle associated with worse quality of life 55 .…”
Section: Discussionmentioning
confidence: 99%